2014
DOI: 10.1155/2014/603097
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Small Bowel Metastasis from Uterine Leiomyosarcoma: A Case Report

Abstract: Background. Uterine leiomyosarcoma is a rare and aggressive gynecologic malignancy with an overall poor prognosis. Lungs, bones, and brain are common sites of metastases of uterine leiomyosarcoma. Metastases of uterine leiomyosarcoma to the small bowel are extremely rare, and only four case reports have been published to date. Case presentation. A 55-year-old Saudi woman diagnosed with a case of uterine leiomyosarcoma treated with total abdominal hysterectomy (TAH) and bilateral salpingooophorectomy (BSO) pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…The propensity of SK‐LMS‐1 cells to spread to distal portions of the CAM mesenchyme as well as to the embryo liver is consistent with the high propensity of vLMS to infiltrate secondary organs .…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The propensity of SK‐LMS‐1 cells to spread to distal portions of the CAM mesenchyme as well as to the embryo liver is consistent with the high propensity of vLMS to infiltrate secondary organs .…”
Section: Discussionsupporting
confidence: 62%
“…In our experimental condition, SK-LMS-1 cells might enable their own growth and spreading by both expressing pro-angiogenic factors and modulating the expression of chick angiogenic factors. The propensity of SK-LMS-1 cells to spread to distal portions of the CAM mesenchyme as well as to the embryo liver is consistent with the high propensity of vLMS to infiltrate secondary organs [4][5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The lungs are the most common site of metastasis, followed by the pelvis, liver, bone, and brain. In a review of the literature, only three other small bowel metastases from uLMS have been reported ( Ben-Ishay et al, 2010 , Saylam et al, 2009 , Tunio et al, 2014 ). Our patient had several metastatic lesions to her small bowel, liver, lung, and brain during the course of her disease.…”
Section: Discussionmentioning
confidence: 99%
“…Lung, liver, peritoneal cavity, pelvic lymph nodes, vertebral and long bones are typically reported sites of recurrent uLMS (7). The array of tools currently available in imaging techniques and the prompt detection in high-risk patients has allowed the identification of more atypical patterns of uLMS recurrence, such as heart, parotid gland, gastrointestinal tract, brain, and skull (8)(9)(10).…”
mentioning
confidence: 99%